Hand and ultrasonic instrumentation in the treatment of chronic periodontitis after supragingival plaque control Instrumentação manual e ultra-sônica no tratamento da periodontite crônica após controle de placa supragengival - Ana Chapper; Viviane Vasconcelos Catão; Rui Vicente Oppermann (Sociedade Brasileira de Pesquisa Odontológica, 2005)
This study compared the clinical effects of hand or ultrasonic scaling and root planing on the treatment of chronic periodontitis. After supragingival plaque control, twenty patients were examined by a blinded and calibrated examiner for probing pocket depth (PPD), clinical attachment level (CAL) and bleeding on probing (BOP). Experimental teeth were allocated to the following subgingival treatment groups according to PPD: 1) hand instrumentation; 2) hand instrumentation with irrigation; 3) ultrasonic instrumentation; 4) ultrasonic followed by hand instrumentation. Time used in the procedures was recorded. Follow-up examinations were performed at 30 and 90 days after treatment. Each patient's individual BOP, PPD and CAL means were analyzed with repeated-measures ANOVA. Differences in the instrumentation time were analyzed with 1-way ANOVA. Significance level was established at 5%. All treatments produced significant changes in the clinical parameters. BOP reduced, in proximal surfaces, from 67.21-79.17% at baseline to 45.75-51.54% at 90 days. Significant reductions were also found for PPD and CAL in all groups, both in proximal and free surfaces. Reductions in mean PPD at 90 days ranged from 0.92 to 1.14 mm for the free surfaces and from 1.01 to 1.35 mm for proximal surfaces, whereas reductions in CAL ranged from 0.43 to 0.82 mm and from 0.60 to 0.73 mm for free and proximal surfaces, respectively. Mean instrumentation time ranged from 4.77 to 5.30 minutes. No statistically significant differences were found among the four study groups. It can be concluded that the four methods of subgingival instrumentation were equally efficacious in the improvement of the studied clinical parameters. Este estudo comparou, clinicamente, o efeito de raspagem e alisamento radicular por instrumentações manual e ultra-sônica no tratamento da periodontite crônica, após o controle de placa supragengival em 20 pacientes. Os parâmetros clínicos profundidade de sondagem (PS), nível de inserção clínica (NIC) e sangramento à sondagem (SS) foram avaliados por um examinador calibrado e cego. Os dentes experimentais foram alocados para uma das seguintes abordagens subgengivais, de acordo com a profundidade de sondagem: 1) manual, 2) manual associada à irrigação, 3) ultra-sônica, 4) ultra-sônica previamente à manual. O tempo usado nos procedimentos foi registrado. Avaliações foram feitas 30 e 90 dias após os tratamentos. Médias individuais de SS, PS e NIC foram analisadas pelo teste ANOVA de medidas repetidas (p < 0,05). Diferenças no tempo de instrumentação foram analisadas por meio do teste ANOVA para um critério de classificação (p < 0,05). Os resultados revelaram que os tratamentos produziram alterações significativas nos parâmetros clínicos sem diferenças estatisticamente significantes entre os quatro grupos. Observaram-se reduções no SS, que, nas faces proximais, variou de 67,21 a 79,17%, no início, para 45,75 a 51,54% no final. Também foram observadas reduções significativas na PS e no NIC em todos os grupos, tanto para faces livres quanto proximais: as médias da PS aos 90 dias reduziram entre 0,92 e 1,14 mm nas faces livres e entre 1,01 e 1,35 mm nas proximais, enquanto para NIC as reduções foram de 0,43 a 0,82 mm e 0,60 a 0,73 mm, para as faces livres e proximais respectivamente. A média do tempo operatório variou de 4,77 a 5,30 minutos. Pôde-se concluir que as quatro modalidades terapêuticas de instrumentação subgengival foram igualmente eficazes na melhora dos parâmetros clínicos estudados.